PEDAGOGICAL CONDITIONS FOR PREPARING FUTURE MATHEMATICS AND COMPUTER SCIENCE TEACHERS FOR THE USAGE OF VIRTUAL CLARITY TOOLS IN PROFESSIONAL ACTIVITIES - Mulesa, Pavlo; Semenikhina, Olena (Physical and Mathematical Education, 2023)
Formulation of the problem. A comprehensive study of the problem of professional training of specialists requires clarification of the relevant conditions for its implementation. The general feature of all the requirements for the organization of educational activities is that they are explicitly created, making it possible to build a holistic model of the pedagogical system of education and fill its components with specific content. We are developing a pedagogical system of professional training for future teachers of mathematics and computer science for the use of virtual clarity tools in professional activity. Therefore, the question of determining the pedagogical conditions for its implementation is relevant. Therefore, the purpose of the article is to determine the pedagogical conditions for preparing future teachers of mathematics and computer science for the use of virtual clarity in professional activities.Materials and methods. To achieve the goal, theoretical (analysis and generalization of scientific sources, terminological analysis, structural and logical analysis) and empirical (survey, expert assessment) methods of scientific knowledge were used.Results. The preparation of future teachers of mathematics and computer science for the use of virtual visual aids in professional activities requires compliance with pedagogical conditions: 1) the strengthening of the motivation to use virtual clarity tools; 2) the active usage of computer visualization tools in the process of studying professionally oriented disciplines; 3) the development of the ability to introduce innovations in the field of virtual clarity tools.Conclusions. The separation of pedagogical conditions for the preparation of future mathematics and computer science teachers for the use of virtual clarity tools in professional activities makes it possible to justify the modernization of their professional training and introduce these conditions into the educational process.
Keywords: professional training; future teachers of mathematics and computer science; usage the virtual clarity; professional education; pedagogical conditions